EFFECT OF ENVIRONMENTAL TOXICITY ON REPRODUCTIVE SYSTEM: A REVIEW - Baidya, Amrita (International Journal of Ayurveda and Pharma Research, 2019)
Reproductive toxicity is the toxicity of reproductive system caused due to environmental factors such as chemicals, heavy metals etc. They interfere in some way with normal reproduction, such substances are called reprotoxic. It includes hazardous effects on fertility and sexual function in adult males and females as well as developmental toxicity in the offspring. Developmental toxicity is abnormal structure or functional development following exposure of pregnant or lactating females. In environment there are various factors which are responsible for causing adverse effect on reproductive system. Heavy metals like cadmium, lead, mercury, Industrial chemicals like phthalates, BPA, Agricultural chemicals, radiations, some of the narcotics drugs like morphine, ethanol, psychotropic drugs like diazepam, chlorpromazine, hypotensives like methyldopa, reserpine. All these factors acts as reproductive toxicants and affects male and female reproductive system causing spontaneous abortion, miscarriage, reduced fertility, preterm delivery, LBW, affect sertoli cells in the testis, affect leydig cell function etc. In ancient Ayurvedic texts also it is described that the heavy metal such as mercury, copper affects the reproductive system. Metals and metallic compounds, pesticides, some food additives have a nature of accumulations within the living body when it exposed since prolonged period. These factors accumulate in the body day by day. This is nothing but Dushivisha (cumulative toxins). Dushivishas vitiates the Dhatus after the laps of a long time on obtaining a favorable condition. It also affects the Shukradhatu causing Shukrashaya (diminish semen). People should be aware of all these factors to take adequate precaution.